Cosmological lensing ratios with DES Y1, SPT, and Planck. Issue 1 (14th May 2019) - Prat, J; Baxter, E; Shin, T; Sánchez, C; Chang, C; Jain, B; Miquel, R; Alarcon, A; Bacon, D; Bernstein, G M; Cawthon, R; Crawford, T M; et al.
ABSTRACT: Correlations between tracers of the matter density field and gravitational lensing are sensitive to the evolution of the matter power spectrum and the expansion rate across cosmic time. Appropriately defined ratios of such correlation functions, on the other hand, depend only on the angular diameter distances to the tracer objects and to the gravitational lensing source planes. Because of their simple cosmological dependence, such ratios can exploit available signal-to-noise ratio down to small angular scales, even where directly modelling the correlation functions is difficult. We present a measurement of lensing ratios using galaxy position and lensing data from the Dark Energy Survey, and CMB lensing data from the South Pole Telescope and Planck, obtaining the highest precision lensing ratio measurements to date. Relative to the concordance ΛCDM model, we find a best-fitting lensing ratio amplitude of A = 1.1 ± 0.1. We use the ratio measurements to generate cosmological constraints, focusing on the curvature parameter. We demonstrate that photometrically selected galaxies can be used to measure lensing ratios, and argue that future lensing ratio measurements with data from a combination of LSST and Stage-4 CMB experiments can be used to place interesting cosmological constraints, even after considering the systematic uncertainties associated with photometric redshift and galaxy shear estimation.